2014
DOI: 10.1310/hpj4910-913
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel, Carboplatin, and Trastuzumab

Abstract: The complexity of cancer chemotherapy requires pharmacists be familiar with the complicated regimens and highly toxic agents used. This column reviews various issues related to preparation, dispensing, and administration of antineoplastic therapy, and the agents, both commercially available and investigational, used to treat malignant diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…A significant benefit was still observed at 4 years with an improved DFS (13), and at 11 years with improved DFS and OS (14). Subgroup analysis from clinical trials showed that the benefits associated with trastuzumab were independent of tumor size and lymph node positivity (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…A significant benefit was still observed at 4 years with an improved DFS (13), and at 11 years with improved DFS and OS (14). Subgroup analysis from clinical trials showed that the benefits associated with trastuzumab were independent of tumor size and lymph node positivity (15,16).…”
Section: Introductionmentioning
confidence: 99%